Modal and Vibration Analysis on Railway Viaduct Structure - Mohd Yunus, Nurul Nabila; Azmir, Nor Azali (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This paper investigates the vibration modes, boundary conditions, natural frequency, and harmonic response of the viaduct structure. By using ANSYS software, two different analysis need to be measured which are modal analysis and vibration analysis. Finite Element Analysis is used to verify natural frequencies and boundary conditions for the vibration of the bridge. Modal analysis is used to determine the meshing of the geometry, material properties (structural steel and concrete) and natural frequency, and mode shape of the viaduct. The twenty-mode shape are deformed as results from the natural frequency. The vibration analysis is used to measure the harmonic response and boundary conditions including fixed support and forces on the railway viaduct. The frequency range that acting on the viaduct is between 0 Hz to 50 Hz for five intervals. At 50 Hz, the deformation of the bridge is appeared after solving in the simulation software